REORIENTATION OF THE ULTIMUM REMEDIUM PRINCIPLE IN HANDLING ECONOMIC CRIME REGARDING PROTECTIVE EQUIPMENT AND COVID-19 MEDICATIONS - Christianto, Hwian (Jurnal Bina Mulia Hukum, 2023)
Applying the ultimum remedium principle to economic crimes needs to be studied from a regulatory perspective concerning the situation during the Covid-19 pandemic. The normative juridical research method combines a statutory approach with a conceptual approach. Both approaches provide a comprehensive understanding of the ultimum remedium principle in legislation and a contextual understanding of economic crimes during the Covid-19 pandemic. The results show that Emergency Law 7/1955 applies the primum remedium principle with a double-track punishment system, while Trade Law applies the ultimum remedium principle. Handling economic crimes related to providing personal protective equipment and/or medications to prevent and recover from Covid-19 infections can be considered essential goods and important commodities are given the situation and conditions during the Covid-19 pandemic in Law Number 7 2014. Applying Trade Law meets the ultimum remedium principle but does not prioritize the recovery of economic losses suffered.